2005
DOI: 10.1111/j.1365-2893.2005.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin treatment of viral hepatitis: a systematic review

Abstract: Silymarin from the milk thistle herb (Silybum marianum) is used by many patients with chronic viral hepatitis, but its efficacy remains unknown. We performed a systematic review of silymarin for the treatment of chronic viral hepatitis B and C. An exhaustive search strategy identified 148 papers that studied silymarin compounds in liver disease. Of these, four trials included patients with hepatitis C, one included hepatitis B patients, and two, unspecified chronic viral hepatitis. However, only one trial excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
108
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 48 publications
2
108
1
1
Order By: Relevance
“…This also was in agreement with Shindo et al who concluded that silymarin treatment resulted in a statistically significant decrease in transaminases in four studies compared with baseline and in one compared with placebo in patients with chronic viral hepatitis (Shindo, Hamada, et al 2001). If silymarin does indeed lower ALT levels and help achieve a biochemical response, it may also act synergistically with interferon to increase the rates of sustained virological response, but this hypothesis has yet to be clinically investigated (Mayer, Myers, et al 2005). …”
Section: Discussionsupporting
confidence: 79%
“…This also was in agreement with Shindo et al who concluded that silymarin treatment resulted in a statistically significant decrease in transaminases in four studies compared with baseline and in one compared with placebo in patients with chronic viral hepatitis (Shindo, Hamada, et al 2001). If silymarin does indeed lower ALT levels and help achieve a biochemical response, it may also act synergistically with interferon to increase the rates of sustained virological response, but this hypothesis has yet to be clinically investigated (Mayer, Myers, et al 2005). …”
Section: Discussionsupporting
confidence: 79%
“…Other agents known to lower aminotransferase activity such as silymarin and ribavirin (when used alone) do not have significant effects on disease progression. 19,20 However, these agents lower aminotransferase activity much more slowly and presumably by different mechanisms. Longer studies with IDN-6556 are needed to determine whether it can affect endpoints such as serum markers of apoptosis, inflammation, and fibrosis on liver biopsy and ultimately clinical outcomes of chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Évtizedek óta szerepel az alkoholos májbetegség terápiás eszköztá-rában [1,15], de HCV-infekcióban is alkalmazták, ellentmondó -de leginkább negatív -eredményekkel [22]. Hazai placebokontrollos tanulmányunkban a P/R antivirális terápia szilimarinnal történő kiegészítésének hatását, az oxidatív stressz és a virológiai válasz (SVR) alakulását vizsgálva nem tudtuk igazolni a fl avonoidkomplex-szupportáció előnyét [18].…”
Section: Inzulinrezisztencia (Ir) éS Steatosisunclassified